Stoichiometric Characteristics of Carbon, Nitrogen, and Phosphorus in Leaves of Differently Aged Lucerne (Medicago sativa) Stands - Wang, Zhennan; Lu, Jiaoyun; Yang, Mei; Yang, Huimin; Zhang, Qingping (Frontiers in Plant Science, 2015)
Element concentration within a plant which is vital to function maintenance and adaptation to environment, may change with plant growth. However, how carbon (C), nitrogen (N), and phosphorus (P) vary stoichiometrically with stand growth, i.e., ages or cuts, was still untouched in perennial species. This study tested the hypothesis that lucerne (Medicago sativa) C:N, C:P, and N:P should change with stand age and cut. Leaf C:N, C:P, and N:P changed with stand age, showing various trends in different cuts of lucerne. Generally the greatest stoichiometric ratios were measured in 8 year stand and in the second cut. They were affected significantly and negatively by total N and P concentrations of leaf, but not by organic C concentration. There were significantly positive correlations among leaf C:N, C:P, and N:P. However, leaf C:N, C:P, and N:P were hardly affected by soil features. Conclusively, lucerne C, N, and P stoichiometry are age- and cut-specific, and regulated mainly by leaf N, P concentrations and stoichiometry. There are few correlations with soil fertility. To our knowledge, it is the first try to elucidate the stoichiometry in the viewpoint of age and cut with a perennial herbaceous legume.